DEVELOPMENT OF STRENGTH TRAINING MODELS IN CHILDREN AGED 8–10 YEARS BASED ON TRADITIONAL LOCAL GAMES IN GORONTALO PROVINCE - Kadir, Suprianto; Haryani, Meri; AF, Oca Fernandes; Toniyo, Nazzarudin (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
This study aims to develop a strength training model for children aged 8-10 years based on local traditional games in the form of a guidebook. This research uses the Research & Development method. This method is used to produce certain products and test the effectiveness of these products. In this research, the test subjects that will be used are children aged 8-10 years who are in the Botu Village, Dumbo Raya District, Gorontalo City. This study uses an assessment questionnaire based on the number of opinions or answers to the questionnaire with a percentage. Percentages are intended to determine the status of something that is presented and presented in the form of a percentage. Based on the results of the trial which was carried out in two stages, namely from the small group trial to the large group trial, there was a decrease in the content feasibility aspect from 90% to 84.3%, the grammar aspect from 84.16% to 81.25%, the display aspect 89.16% to 84.06%, then the total assessment results from the small group test to the large group test decreased from 88.77% to 83.78% or it could be said to be a decrease of 4.99%